2021
DOI: 10.1136/bmjopen-2020-041900
|View full text |Cite
|
Sign up to set email alerts
|

Real-world challenges for patients with breast cancer in sub-Saharan Africa: a retrospective observational study of access to care in Ghana, Kenya and Nigeria

Abstract: ObjectiveTo evaluate medical resource utilisation and timeliness of access to specific aspects of a standard care pathway for breast cancer at tertiary centres in sub-Saharan Africa.DesignData were retrospectively abstracted from records of patients with breast cancer treated within a prespecified 2-year period between 2014 and 2017. The study protocol was approved by local institutional review boards.SettingSix tertiary care institutions in Ghana, Kenya and Nigeria were included.ParticipantsHealth records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The stage at diagnosis was reported in 7/13 studies 25–27,30,33–36 ; histopathology data were found in all the studies except two, 25,35 and hormonal status in 5 out of 13 studies 26,27,30,33,34 . Data about the CT use were in all the studies except one 29 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The stage at diagnosis was reported in 7/13 studies 25–27,30,33–36 ; histopathology data were found in all the studies except two, 25,35 and hormonal status in 5 out of 13 studies 26,27,30,33,34 . Data about the CT use were in all the studies except one 29 .…”
Section: Resultsmentioning
confidence: 97%
“…Bilateral therapeutic mammoplasty in most of the patients (222/251) was reported by Grubnick et al (2013); BCS was traced in two studies of South Africa 28 . BCS (or BCT) was reported in studies performed in Guinea, 25 South Africa, 28–32 Zambia, 33 and in an international multicenter study conducted in Ghana, Kenya, and Nigeria 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…East African countries, for instance, Kenya, offer lessons in reducing financial toxicity of cancer treatment. 59 High out-of-pocket payments for care are an impediment to treatment compliance and cancer control in SSA, demanding urgent attention. 59 The spiraling costs of cancer care, dwindling health care budgets, and competition for monetary resources all contribute to the financial burden of cancer treatment in SSA.…”
Section: Discussionmentioning
confidence: 99%
“… 8 For example, recent data from Ghana, Nigeria and Kenya indicate that only 21–29% of eligible patients receive AI treatment. 23 …”
Section: Pharmacogenetics Of Breast Cancer In Sub-saharan Africamentioning
confidence: 99%